Research trends in flavonoids and health - Perez Vizcaino, Francisco (2018)
Herein we describe, based on some bibliometric data, how the field of research on flavonoids has evolved over the last 25 years. The number of papers on flavonoids has risen in an exponential manner over these years, much faster than other fields on food constituents. This increase appears to be related to the contemporary explosion of interest in healthy foods, supplements and nutraceuticals. It was also probably triggered by large epidemiological studies on fruits and vegetables, and particularly on flavonoids, consumption and incidence of cancer, stroke and coronary heart disease. The widely distributed flavonols constitute the flavonoid subgroup upon which the greatest interest has been focused, followed by flavanols and more recently by anthocyanidins and other related polyphenols such as resveratrol. Research on isoflavones rapidly emerged in the 1990s but plateaued in the 2000s. In the 1990s flavonoids were mainly considered as the active components of medicinal plants, while from 2000 onward, they switched to be mainly regarded as bioactive food ingredients. We envision a continuation in the growth of research for the coming decade focused on clearly demonstrating the importance of flavonoids for human health.